LEDs: Quasi‐2D Colloidal Semiconductor Nanoplatelets for Narrow Electroluminescence (Adv. Funct. Mater. 3/2014). (January 2014) - Chen, Zhuoying; Nadal, Brice; Mahler, Benoit; Aubin, Hervé; Dubertret, Benoit
<x xml:space="preserve">Abstract</x> In the search for better‐performing colloidal lightemitting diodes (LEDs), nanocrystals of anisotropic morphologies remain to be explored. On page 295, Z. Chen et al. present the first functional LEDs based on quasi‐2D core/shell CdSe/CdZnS nanoplatelets, where quantum confinement takes place in the direction of thickness. These solution‐processed hybrid LEDs exhibit extremely narrow electroluminescence under different driving voltages, which is highly promising to achieve superior color purity. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>